Effects of Yam Powder Produced by Different Drying Ways on the Quality and Antioxidant Activity of Greek Style Yogurt during Refrigeration - Rongkun MA; Zhongyi ZHANG; Shangzhen CHENG (Shipin gongye ke-ji)
To study the effect of yam powder produced by different drying processes (hot air, microwave, and freeze drying) on the quality stability and antioxidant activity of Greek style yogurt during storage, the three types of yam powder were used to replace 2% whole milk powder to make Greek style yogurt, and the changes of various indicators were determined during 21 d of storage at 4 ℃. The results showed that with an increase in storage time, the indicators of Greek style yogurt, such as acidity, hardness, cohesion, viscosity, number of lactic acid bacteria, and polyphenol content, increased to some extent, the solid content and water retention decreased slightly, and the iron reduction capacity and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical clearance rate were basically in a stable state. Compared to the blank (control) group, the three types of yam powder significantly increased the acidity, cohesion, viscosity, polyphenol content, iron reducing ability, and DPPH radical scavenging rate of Greek style yogurt (P<0.05), increased the water holding capacity and lactic acid bacteria count to some extent, but significantly reduced its total solid content (P<0.05). However, the hardness value of the yam Greek style yogurt was relatively high before 14 d of storage, and after 21 d of storage was lower than that of the blank (control) group. During refrigeration, the three types of yam yogurt exhibited notable disparities in various indicators, including solid content, hardness, cohesion, and viscosity (P<0.05). Notably, the solid content of the Y3 group (freeze drying) was significantly elevated compared to both the Y1 group (hot air drying) and the Y2 group (microwave drying) (P<0.05). Conversely, the hardness of the Y3 group was notably lower than that of the Y1 group and Y2 group (P<0.05). Furthermore, the Y3 group exhibited slightly superior values in acidity, iron reduction capacity, and DPPH radical clearance rate compared to the Y1 group and Y2 group. The cohesion and viscosity of the Y3 group and Y2 group were significantly greater than those of the Y1 group (P <0.05). Based on the comprehensive analysis, among the three types of yam powder, freeze-dried yam powder was more conducive to improving the quality and antioxidant performance of Greek style yogurt. This study would provide a theoretical basis for the application of yam powder in Greek style yogurt.